Both the COMT Val158Met single-nucleotide polymorphism and sex-dependent differences influence response inhibition - Mione, Valentina; Canterini, Sonia; Brunamonti, Emiliano; Pani, Pierpaolo; Donno, Federica; Fiorenza, Maria Teresa; Ferraina, Stefano (Frontiers in Behavioral Neuroscience, 2015)
Reactive and proactive control of actions are cognitive abilities that allow to deal with a continuously changing environment by adjusting already programmed actions. They also set forthcoming acts by evaluating the outcome of the previous ones. Earlier studies highlighted sex related differences in the strategies and in the pattern of brain activation during cognitive tasks involving reactive and proactive control. To further identify sex-dependent characteristics in the cognitive control of actions, in this study we have assessed whether/how differences in reactive and proactive control were modulated by the COMT Val158Met single nucleotide polymorphism, a genetic factor known to influence the functionality of the dopaminergic system, in particular at the level of prefrontal cortex. Two groups of male and female participants were further sorted according to their genotype (Val/Met, Val/Val and Met/Met) and tested in a stop signal task, a consolidated tool to measure reactive and proactive control in experimental and clinical settings. In each group of participants we estimated both a measure of the capacity to react to unexpected events and the ability of monitoring their performance. The between groups comparison of these measures indicated a poorer ability of male individuals carrying the Val/Val genotype in error-monitoring, suggesting that differences between sexes could be influenced by the efficiency of COMT and that other sex-specific factors have to be considered. The comprehension of inter-groups behavioral and physiological correlates of cognitive control will provide more accurate diagnostic tools for predicting the incidence and the development of pathologies like ADHD or deviant behaviors as drug or alcohol abuse.